(untitled) (Bioscience Journal, 2020)
The medicinal and aromatic species Lantana camara is a bush that receives a lot of interest regarding ornamental use. However, due to its condition of invasive plant in natural environments, it suffers constant eradication attempts, which causes genetic erosion of the species. To work around this problem, a sample of the genetic variability of L. camara was saved in the Active Germplasm Bank of medicinal and aromatic plants of the Federal University of Sergipe (UFS). This study aimed to evaluate morphoagronomically 22 accessions of L. camara, collected in 15 municipalities in the state of Sergipe. To carry out morphoagronomic characterization, morphological and agronomic traits were analyzed. Phenotypic variability among the accessions of the L. camara collection for all the analyzed morphological quantitative and agronomic characteristics was observed. The means ranged from 4.91 to 6.90 cm for leaf length; from 2.81 to 5.03 cm for leaf width; from 1.32 to 1.87 for the leaf length/width ratio; from 9.59 to 22.98 mm2 for leaf area; from 99.00 to 215.00 cm for crown diameter; from 85.67 to 214.33 for plant height; and from 1.08 to 2.43 cm for stem diameter. Most accessions presented erect form. The mean number of flowers per inflorescence varied from 12 to 38 flowers. For the agronomic traits, we observed that the dry mass ranged from 49.86 to 649.04 g.plant-1. The mean content of essential oil ranged from 0.13 to 0.26% and yield between 0.10 and 1.55 mL.plant-1. The most divergent phenotypic accessions were LAC-001 (São Cristóvão) and LAC-038 (Moita Bonita) and the ones with the lowest divergence were LAC-004 (Itaporanga D’ajuda) and LAC-019 (Siriri). Thus, it was observed that the variables were efficient to differentiate the accessions and suggest the existence of genetic variability among them.